The Yemen Houthi-Saudi Conflict: Iran’s Strategic Influence and the Impact of Disruptive Technologies - Muhammad Waseem (Social Science Review Archives, 2025)
This paper seeks to investigate the Houthi-Saudi Conflict in Yemen through the lens of disruptive technology infusion to modern warfare and the strategic influence of Iran. It examines how Yemen, a historically divided and struggling country, became an arena for proxy powers, particularly Iran and Saudi Arabia. Iran has made the Houthis more than a local militia; the rebels are now an effective military force with drones, ballistic missiles and cyberweapons that represent a major threat to regional security. The war has destroyed Yemen’s humanitarian infrastructure and placed a chokehold on maritime commerce in the Red Sea, destabilizing the geopolitics of the Middle East. Citing UN reports, expert assessments and real-time data, the report says the war is no longer a border conflict but a “blueprint” for future asymmetric warfare between non-state actors backed by external states. The article concludes by arguing the necessity of technological containment, multilateral diplomacy, and inclusive political reconciliation for a resolution of the crisis.